General and regional elections in Guyana, 15 December 1997 (Commonwealth Secretariat LondonGB, 1998)
Focuses on the organisation and conduct of the elections in accordance with the Laws of Guyana. Considers the various factors impinging on the credibility of the electoral process as a whole. Seeks to see whether the conditions existed for a free expression of will by the electors and if the result of the elections reflected the will of the people.
DC